2011
DOI: 10.1016/j.etp.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on lipid peroxidation and antioxidative enzyme activities in the liver, kidneys and brain of rats administered with benzo(a)pyrene

Abstract: Podhorska-Okolów, et al.. Effects of melatonin on lipid peroxidation and antioxidative enzyme activities in the liver, kidneys and brain of rats administered with benzo(a)pyrene. Experimental and Toxicologic Pathology, Elsevier, 2010, 63 (1-2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Melatonin attenuated the decrease in the activities of superoxide dismutase, catalase and glutathione peroxidase in the brain, liver and kidneys of mice treated with zymosan (Szaroma and Dziubek, ), induced SOD2 expression in the brain of aged mice and improved the mitochondrial population and function in old mice (García‐Macia et al, ). Melatonin augmented the activities of superoxide dismutase and catalase in liver, kidneys and brain of rats treated with benzo(a)pyrene (Murawska‐Ciałowicz et al, ). Circadian variations in the level of melatonin may control the activity of catalase and superoxide dismutase in a tropical bird Perdicula asiaticam via the nuclear RORalpha receptor (Kharwar and Haldar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin attenuated the decrease in the activities of superoxide dismutase, catalase and glutathione peroxidase in the brain, liver and kidneys of mice treated with zymosan (Szaroma and Dziubek, ), induced SOD2 expression in the brain of aged mice and improved the mitochondrial population and function in old mice (García‐Macia et al, ). Melatonin augmented the activities of superoxide dismutase and catalase in liver, kidneys and brain of rats treated with benzo(a)pyrene (Murawska‐Ciałowicz et al, ). Circadian variations in the level of melatonin may control the activity of catalase and superoxide dismutase in a tropical bird Perdicula asiaticam via the nuclear RORalpha receptor (Kharwar and Haldar, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the findings showed oxidative stress and DNA damages in kidney induced by B[a]P. The stomach is also exposed to exogenous carcinogens such as B[a]P which is used to induce tumors in the lung, skin, and forestomach of mice ( Lee et al., 2005 ). Experimental data have demonstrated that B[a]P easily crosses the blood-brain barrier and induces acute neurobehavioral toxicity through oxidative stress ( Murawska-Ciałowicz et al., 2011 ). Thus, the results also indicated oxidative stress and DNA damage in stomach and brain.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that expression and activity of Cu,Zn‐SOD and cytosolic and mitochondrial GPx increase in parallel to a reduced concentration of TBARS and to a lowered GSSG/GSH ratio in the liver of aging rats treated with melatonin [35]. It has also been found that melatonin induces rises in liver GSH and SOD activity in rats administered with benzo(a)pyrene [39] or prevents the decrease of GPx activity and the rise in TBARS concentrations in rats treated with carbon tetrachloride [13].…”
Section: Discussionmentioning
confidence: 99%